Rocks and ore of PGE-bearing Vuruchuaivench massif (Kola Peninsula, Russia) - Pakhalko, Aleksey (Geology, Geophysics and Environment, 2015)
The Vuruchuaivench massif is part of the Monchegorsk pluton and located in center of Kola Peninsula. The massif is known for its PGE mineralization with an average of 2-2.5 ppm PGE, samples containing 19 ppm are also found. Main rocks of massif – metasomatized gabbronorites and anortosites.  Presence of metasomatic propylite rock was for the first time established in the territory. Two propylite groups that differ by mineral composition were identified. PGE mineralization is associated with quartz-chlorite-albite group; mineralization is not related with another - albite group. There is a difference in the total REE content in gabbronorites and propylites. Closeness of graphs REE concentrations in all rocks array may indicate their genetic relationship. Among platinum group minerals in ore of Vuruchuaivench massif prevail arsenides and sulphoarsenides. Age of propylites (Rb-Sr isotopic system) is 2,470 ± 130 Ma. Isotopic data indicate a slight part of a crustal component in formation of rocks and ores of Vuruchuaivench massif.